WOMEN'S PARTICIPATION IN VILLAGE CONSULTATIVE BODY RECRUITMENT IN CENTRAL WOLOGAI VILLAGE IN 2019 - Seran, Maria Florida Suryani; Boro, Veronika Ina Assan (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2024)
The Village Consultative Body (BPD) is the embodiment of village democracy. Democracy means that in administering government and development it must always pay attention to the aspirations of the community which are articulated and aggregated by the BPD and other social institutions. In the context of the existence of BPD, women need to have representatives in the formulation and determination of policies, this model is referred to as representative, and is also able to influence the process and substance of public policy, referred to as influence participation. The representation of women in the membership of the Village Consultative Body (BPD) is very important to oversee women's aspirations so that they become village public policy. The aim of this research is to find out how women participate in recruiting members of the Village Consultative Body (BPD) in Central Wologai Village. Qualitative descriptive methods were used in this research. The figure of 30% as a critical minority is the minimum quota limit for women in government institutions in accordance with the 1995 UN Development Report which analyzed gender and development in 17 countries. The findings in this study show that recruitment of Village Consultative Body (BPD) members in Central Wologai village shows that women's representation has increased from the minimum limit of 30%. The results of the recruitment of BPD members showed that women's representation reached 64.1%.